ChemInform Abstract: Oxidative Olefination of Anilides with Unactivated Alkenes Catalyzed by an (Electron‐Deficient η5‐Cyclopentadienyl)Rhodium(III) Complex under Ambient Conditions. Issue 44 (15th October 2015) - Takahama, Yuji; Shibata, Yu; Tanaka, Ken
Abstract The oxidative olefination of anilides with both activated and unactivated alkenes using an (electron‐deficient η5‐cyclopentadienyl)rhodium(III) complex leads to mono‐olefinated products (III) and (VI) as main products.